Effects of extrusion on Young’s modulus and internal friction of magnesium alloys with various long period ordered structure content - Vladimir V. Kaminskii; Dmitrii A. Kalganov; Maksim V. Dorogov; Sergei A. Philippov; Alexey E. Romanov (Frontier Materials & Technologies)
The relevance of this work stems from the growing interest in magnesium alloys with long period ordered structure (LPSO) due to their unique mechanical properties. Investigating the effect of extrusion on Young’s modulus and internal friction of such alloys provides a deeper understanding of their mechanical behaviour, which is important for the development of new materials with improved performance properties. This research explores the effect of warm extrusion on the structure, dynamic Young’s modulus and internal friction of magnesium alloys containing varying amounts of LPSO phases. Alloys in the Mg–Zn–Y system with estimated LPSO phase contents of 0, 50 and 100 % vol. were analysed using the composite piezoelectric oscillator technique at 100 kHz. The results demonstrate that the Young’s modulus increases with higher LPSO content, driven by the enhanced stiffness and strong interatomic bonding of the LPSO phases. Extrusion leads to a 3 % decrease in Young’s modulus along the direction parallel to its axis for all samples. This effect is explained by the formation of an elongated texture and an increase in the dislocation density. Internal friction measurements revealed a rise in amplitude-independent internal friction post-extrusion, suggesting higher dislocation density, while the critical strain amplitude decreased in alloys with higher LPSO content. Additionally, Young’s modulus softening was reduced after extrusion, primarily due to dislocation-induced hardening. These findings shed light on the mechanical properties of Mg–Zn–Y alloys with LPSO structures, emphasising the effects of extrusion and phase content on their dynamic behaviour.